Effectiveness and Safety of Infliximab in Two Cases of Severe Chondrocalcinosis: Nine Years of Follow-Up. (10th November 2014) - Bruges-Armas, Jácome; Bettencourt, Bruno F.; Couto, Ana R.; Lima, Manuela; Rodrigues, Ana M.; Vastesaeger, Nathan; Brown, Matthew A.
Abstract : Objectives . To investigate the efficacy of infliximab in the treatment of severe calcium pyrophosphate deposition diseases (CPPD). Methods . Two patients with severe CPPD and diffuse idiopathic skeletal hyperostosis- (DISH-) like phenotype are described. Both patients were resistant to therapy with nonsteroidal anti-inflammatory drugs (NSAIDs). Both patients were treated with infliximab, a TNF- α receptor antagonist, for nine years. Results . Treatment with infliximab resulted in major clinical and laboratory improvements without relevant side effects. Conclusions . These results suggest that infliximab may be an effective treatment of severe CPDD.